Investigação das propriedades ópticas de ZnO e ZnO:Al - Trindade, Neilo Marcos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis presents a study of the optical properties of thin films of pure ZnO and ZnO doped with Al; and a study of the influence of argon gas pressure of argon gas pressure variation during synthesis of films on the optical and structural properties. The films were deposited on glass and silicon substrate by RF magnetron suputtering technique with a target Zn-Al alloy with a concentration of 2% by weight of aluminum. The XRD analysis of the film showed a preferential peak in the (002) - c axis, showing the formation of a wurtzite structure corresponding to the ZnO, and that there is an increase in crystalline size with. Al doping, in agreement with results AFM. Measurements showed the characteristic. Raman vibration mode ZnO around 575 cm-1 and the improvement of crystallinity of the material with the doping of Al, without impairment to the variation of argon pressure. The films exhibited optical transmittance above 70% in the visible spectrum range (400 to 700 nm) and correlated with the reflectance spectrum enabled to obtain data such as the optical band gap in the range 3.5 to 3.6 eV which are above the values obtained for the intrinsic ZnO (3.3 eV). The optical gap results were correlated data obtained through Computational Modeling. The photoluminescence measurements showed a large light emission range in the visible region and emission lines at 3.32 and 3.37 eV suggest that Al doping effect. The optical resuts correlated with the computational modeling reinforce the Burstein-Moss effect is dominant for that material

Este trabalho apresenta um estudo das propriedades ópticas de filmes finos de ZnO puro e de ZnO dopado com Al; e um estudo da influência da variação de pressão do gás argônico durante a deposição dos filmes, nas propriedades ópticas e estruturais. Os filmes foram depositados em substrato de vidro e silício pela técnica RF magnetron sputtering com alvo de uma liga de Zn-Al, com uma concentração de 2% em peso de alumínio. As análises de DRX dos filmes apresentam um pico preferencial no plano (002) - eixo c, que mostra a formaão de uma estrutura de wurtzita correpondente ao ZnO, e que há um aumento do tamanho do cristalino com a dopagem de Al, em concordância com resultados de AFM. Medidas Raman mostram o modo de vibração característico do ZnO ao redor de 575 cm-1 e a melhora da cristalinidade do material com a dopagem de Al, sem a deterioração com a variação de pressão de argônio. Os filmes apresentam valores de transmitância óptica acima de 70% na faixa do visível do espectro (400 a 700 nm) e correlacionados com o espectro de refletância possibilitaram obter dados como o gap óptico na ordem de 3,5 - 3,6 eV, que estão acima dos valores esperados para o ZnO intrínseco (3,3 eV). Os resultados de gap óptico foram correlacionados com dados obtidos através de Modelagem Computacional (DFT). As medidas de fotoluminescência mostram uma larga faixa de emissão de luz na região visível e linhas de emissão em 3,32 e 3,37 eV que sugerem efeito de dopagem de Al. Os resultados de medidas ópticas correlacionadas com a modelagem computacional reforçam que o efeito Burstein-Moss é dominante para esse material
Investigation of the optical properties of ZnO and ZnO:Al
Keywords: Óxido de zinco; Propriedades oticas; Modelagem computacional; Magnetrons; Zinc oxide